Analisis cacat produk pada proses produksi Arm Rear Brake di PT. Ciptaunggul Karya Abadi. - Pujoseno, Rauffan (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2023)
PT. Ciptaunggul Karya Abadi is a private company that manufactures metal stamping components, tools, and dies. This study aims to control poor product quality by using the FMEA method in the rear brake arm production process. Failure Mode and Effect Analysis (FMEA) is a technique for evaluating the level of reliability of a system to determine the effects of system failures. The method in this study was used to collect data by observing the results of arm rear brake production every March, April, and May 2022. From the results of this analysis, it was found that a process could produce a not-good product that has an RPN value from the highest to the lowest. Blanking Process got a score of 144, spot welding got a score of 112, restrike got a score of 84, bending one got a score of 75, bending two got a score of 32, broaching got a score of 32, and the piercing process got a score of 9. One of the main causes of this bad product is operator error. when operating the machine during the rear brake manufacturing process. Another cause is engine damage that requires regular maintenance.